Research of Marine Oil Well Testing Technology - DENG Yong-hong; ZHAO Li-yong; ZHANG Quan-zhu; HUANG Cheng-yu (Institute of Advanced Engineering and Science, 2013)
For marine oil well testing equipment totally depending on ground long-distance power supply, this article designed a set of DC power supply with small size, light weight, strong versatility, simple operation, electromagnetic compatibility and high intelligence, etc. It realized closed loop coordinated control of PI regulator of voltage and current , rapid adjustment of current , continuous adjustment of voltage and current and output of constant-voltage and constant-current. The power supply is composed of many link voltage power unit which achieved the continuous adjustable transform from single-phase low voltage AC 110V to DC voltage 0—1000V and current 0—10A through square wave pulse phase shifting control for IGBT inverter. The power supply design has innovative designing，advanced technology, superior performance, and has been applied in marine oil well testing industry. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3748